Citri reticulate pericranium-derived extracellular vesicles exert antioxidant and anti-inflammatory properties and enhance the bioactivity of nobiletin by forming EVs-nob nanoparticles - Ma, Ling; Ye, Zimao; Guo, Dongqin; Nie, Chao; Zhou, Zhiqin (Frontiers in Cell and Developmental Biology, 2024)
Plant-driven extracellular vesicles (PEVs) have attracted significant interest due to their natural origin, remarkable bioactivity, and efficacy in drug encapsulation and target delivery. In our work, extracellular vesicles from Citri Reticulate Pericranium (CEVs) were isolated and investigated their physicochemical characteristics and biological activities. We identified the vesicle structures as regular, with a particle size of approximately 200 nm. We also detected large quantities of lipids, proteins, carbohydrates, as well as total phenols and total flavonoids. The rich content of CEVs endows them with significant antioxidant and anti-inflammatory effects, which can notably increase the levels of GSH and effectively promote the activity of antioxidant markers such as SOD, CAT, and GR. Additionally, they can inhibit the level of inflammatory markers like NO and inflammatory biological factors (IL-6, IL-1β and TNF-α). In addition, we successfully synthesized EVs-nob nanoparticles with a 83.75% ± 2.83% encapsulation rate and 2.79% ± 0.02% drug loading, which may enhance the antioxidant and anti-inflammatory effects of nobiletin. Our research provides critical insights into the bioactivity of CEVs and demonstrates the significant potential of PEVs in nanocarrier creation, thereby promoting the advancement of more PEVs for biomedical applications.